Two-Stage Tissue-Expander Breast Reconstruction: A Focus on the Surgical Technique. (10th December 2017) - Bellini, Elisa; Pesce, Marianna; Santi, PierLuigi; Raposio, Edoardo
Abstract : Objective. Breast cancer, the most common malignancy in women, comprises 18% of all female cancers. Mastectomy is an essential intervention to save lives, but it can destroy one's body image, causing both physical and psychological trauma. Reconstruction is an important step in restoring patient quality of life after the mutilating treatment. Material and Methods. Tissue expanders and implants are now commonly used in breast reconstruction. Autologous reconstruction allows a better aesthetic result; however, many patients prefer implant reconstruction due to the shorter operation time and lack of donor site morbidity. Moreover, this reconstruction strategy is safe and can be performed in patients with multiple health problems. Tissue-expander reconstruction is conventionally performed as a two-stage procedure starting immediately after mammary gland removal. Results. Mastectomy is a destructive but essential intervention for women with breast cancer. Tissue expansion breast reconstruction is a safe, reliable, and efficacious procedure with considerable psychological benefits since it provides a healthy body image. Conclusion. This article focuses on this surgical technique and how to achieve the best reconstruction possible.